The Class II KNOX family members KNAT3 and KNAT7 redundantly participate in Arabidopsis seed coat mucilage biosynthesis. (21st February 2022) - Zhang, Yuanyuan; Yin, Qi; Qin, Wenqi; Gao, Han; Du, Jinge; Chen, Jiajun; Li, Huiling; Zhou, Gongke; Wu, Hong; Wu, Ai-Min
Abstract: The production of Arabidopsis seed mucilage involves complex polysaccharide biosynthetic pathways and developmental processes in seed epidermal cells. Although the polysaccharide components of Arabidopsis seed mucilage have been identified, their regulatory mechanism requires further investigation. Here, we show that Class II KNOX gene family members KNAT3 and KNAT7 play an essential role in regulating mucilage production in the early developmental stages of Arabidopsis seeds. Double mutant knat3knat7 resulted in defective seed mucilage production and columellae formation, whereas knat3 showed a normal phenotype compared with wild type, and the mucilage thickness in knat7 was slightly disturbed. Rhamnogalacturonan I (RG-I) and its biosynthetic substrates galacturonic acid and rhamnose were reduced in both the adherent and soluble mucilage of knat3knat7 . Comparative transcriptome analysis on whole seeds suggested that polysaccharide, glucosinolate and anthocyanin biosynthetic pathways were specifically repressed in knat3knat7 . Transient co-expression of KNAT3 and KNAT7 with promoter regions of candidate genes in Arabidopsis protoplasts revealed that both KNAT3 and KNAT7 act as positive regulators of the RG-I biosynthetic gene MUCILAGE-MODIFIED 4 ( MUM4, AT1G53500). Collectively, our results demonstrate that KNAT3 and KNAT7 are multifunctional transcription factors in secondary cell wall development and redundantly modulate mucilage biosynthesis in Arabidopsis seeds. Abstract : Class II KNOX family genes KNAT3 and KNAT7 positively control mucilage biosynthesis in Arabidopsis seeds, demonstrating an additional function in polysaccharide biosynthesis.